Induction of multifunctional human immunodeficiency virus type 1 (HIV-1)-specific T cells capable of proliferation in healthy subjects by using a prime-boost regimen of DNA- and modified vaccinia virus Ankara-vectored vaccines expressing HIV-1 Gag coupled to CD8+ T-cell epitopes. - Goonetilleke, N; Moore, S; Dally, L; Winstone, N; Cebere, I; Mahmoud, A; Pinheiro, S; Gillespie, G; Brown, D; Loach, V; Roberts, J; Guimaraes-Walker, A; et al. (2006)
A double-blind randomized phase I trial was conducted in human immunodeficiency virus type 1 (HIV-1)-negative subjects receiving vaccines vectored by plasmid DNA and modified vaccinia virus Ankara (MVA) expressing HIV-1 p24/p17 gag linked to a string of CD8(+) T-cell epitopes. The trial had two groups. One group received either two doses of MVA.HIVA (2x MVA.HIVA) (n=8) or two doses of placebo (2x placebo) (n=4). The second group received 2x pTHr.HIVA followed by one dose of MVA.HIVA (n=8) or 3x placebo (n=4). In the pTHr.HIVA-MVA.HIVA group, HIV-1-specific T-cell responses peaked 1 week after MVA.HIVA vaccination in both ex vivo gamma interferon (IFN-gamma) ELISPOT (group mean, 210 spot-forming cells/10(6) cells) and proliferation (group mean stimulation index, 37), with assays detecting positive responses in four out of eight and five out of eight subjects, respectively. No HIV-1-specific T-cell responses were detected in either assay in the 2x MVA.HIVA group or subjects receiving placebo. Using a highly sensitive and reproducible cultured IFN-gamma ELISPOT assay, positive responses mainly mediated by CD4(+) T cells were detected in eight out of eight vaccinees in the pTHr.HIVA-MVA.HIVA group and four out of eight vaccinees in the 2x MVA.HIVA group. Importantly, no false-positive responses were detected in the eight subjects receiving placebo. Of the 12 responders, 11 developed responses to previously identified immunodominant CD4(+) T-cell epitopes, with 6 volunteers having responses to more than one epitope. Five out of 12 responders also developed CD8(+) T-cell responses to the epitope string. Induced T cells produced a variety of anti-viral cytokines, including tumor necrosis factor alpha and macrophage inflammatory protein 1 beta. These data demonstrate that prime-boost vaccination with recombinant DNA and MVA vectors can induce multifunctional HIV-1-specific T cells in the majority of vaccinees.